Three new species of the genus Loxoconcha (Crustacea, Ostracoda, Podocopida) from the Okinawa Islands, southern Japan - Dung, Le Doan; Tsukagoshi, Akira (Zootaxa, 2014)
Three new species of Ostracoda, Loxoconcha noharai sp. nov., L. santosi sp. nov. and L. sesokoensis sp. nov., are described from the Okinawa Islands, southern Japan. The two species Loxoconcha noharai sp. nov. and L. santosi sp. nov. live in estuaries, whereas the species L. sesokoensis sp. nov. lives in coral reefs. These species can be easily distinguished from other previously described Loxoconcha species by their morphological differences, mainly in the male copulatory organ, and distribution pattern of their pore systems. In addition, L. sesokoensis sp. nov. is suggested to be phylogenetically apart from any other Loxoconcha species which have been reported so far from Japan and the adjacent seas.